PENGARUH LINGKUNGAN TERHADAP KEBERHASILAN UMKM DI DAERAH LAPANGAN DRACIK KAMPUS BATANG - Setianingrum, Evie; Hermawan Adinugraha, Hendri (Bapelitbang Kabupaten Batang, 2024)
This research aims to investigate the influence of the environment on the success of Micro, Small and Medium Enterprises (MSMEs) in the Dracik Field Area, Batang Campus. The research method used was a survey with a questionnaire as a data collection instrument. Respondents are owners and managers of MSMEs operating in the area. The data analysis technique uses multiple linear regression to find out how much influence environmental variables have on the success of MSMEs. The research results show that the environment, such as infrastructure, market access, government policies, and social support, has a significant influence on the success of MSMEs. Adequate infrastructure and broad market access help MSMEs increase product production and distribution. Apart from that, government policies that support MSMEs and social support from local communities also contribute to the growth and success of MSMEs in the area. This research provides a deeper understanding of the environmental factors that influence the success of MSMEs, so that it can become a basis for the government and other stakeholders in designing policies and programs that support the growth of MSMEs in the Dracik Field area, Batang Campus. Keywords: Environment, Economy, and MSMEs.